A structural model of customer satisfaction and trust in vendors involved in mobile commerce - Norazah Mohd Suki (International Journal of Business Science & Applied Management (IJBSAM), 2011)
The purpose of this paper is to provide an explanation of factors influencing customer satisfaction and trust in vendors involved in mobile commerce (m - commerce). The study sample consists of 200 respondents. Data were analyzed by employing structural equation modelling (SEM) supported by AMOS 5.0 with maximum likelihood estimation in order to test the proposed hypotheses. T he proposed model was empirically tested and results confirmed that users' satisfaction with vendors in m-commerce was not significantly influenced by two antecedents of the vendor's website quality: interactivity and customisation, and also two antecedent s of mobile technology quality: usefulness and ease - of - use. Meanwhile, users' trust towards the vendor in m - commerce is affected by users' satisfaction with the vendor. Interestingly, vendor quality dimensions such as responsiveness and brand image influen ce customer satisfaction with vendors in m-commerce. Based on the findings, vendors in m-commerce should focus on the factors which generate more satisfaction and trust among customers. For vendors in general, the results can help them to better develop cu stomer trust in m-commerce. Vendors of m-commerce can provide a more satisfying experience for customers.
Keywords: 650; mobile; m-commerce; trust; satisfaction; structural equation modelling